Engineering chimeric antigen receptor CD4 T cells for Alzheimer’s disease - Pavle Boskovic; Rotem Shalita; Wenqing Gao; Hailey Vernon; Yu Lin Deng; Marco Colonna; Robbie G. Majzner; Ido Amit; Jonathan Kipnis (Proceedings of the National Academy of Sciences, 2026)
Alzheimer’s disease (AD) is the prevailing cause of age-associated dementia worldwide. Current standard of care relies on antibody-based immunotherapy. However, antibody-based approaches carry risks for patients, and their effects on cognition are marginal. Increasing evidence suggests that T cells contribute to AD onset and progression. Unlike the cytotoxic effects of CD8 + cells, CD4 + T cells capable of regulating inflammation show promise in reducing pathology and improving cognitive outcomes in mouse models of AD and in aging. Here, we sought to exploit the beneficial properties of CD4 + T cells while circumventing the need for TCR and peptide–MHC antigen discovery, thereby providing a potential universal therapeutic approach. To achieve this, we engineered CD4 + T cells with chimeric antigen receptors (CARs) targeting fibrillar forms of aggregated amyloid-β. Our findings demonstrate that optimized CAR-T cells can alter amyloid deposition in the dura and reduce parenchymal pathology in the brain. Furthermore, we observed that CAR-T treatment promotes the expansion and recruitment of endogenous CD4 + T cells into the brain parenchyma and leptomeninges. In summary, we established the feasibility of amyloid plaque–specific CAR-T cells as a potential therapeutic avenue for AD. These findings highlight the potential of CD4 + CAR-T therapy not only to modify amyloid pathology but also to reshape the immune landscape of the CNS, paving the way for future development of cellular immunotherapies for neurodegenerative disease.